CONSTRUCTION OF KNOWLEDGE AND DEVELOPMENT OF MULTIPLE INTELLIGENCE TEACHING AND ASSESSING THROUGH PBL - Mody, A.K. (SCHOOL SCIENCE, 2011)
In this paper, we shall discuss constructivist method that is tried successfully to teach students physics using problems. We shall discuss how such a method can help to develop multiple intelligence of students and can also be used for dynamic assessment, that is assessing the students while they learn.